Morphophysiological responses of forage plants under crop and grazing management: A review (Research, Society and Development, 2021)
Brazilian livestock promotes food security and economic stability for producers, representing a large number of specified agribusiness, with strong participation in the gross domestic product, as well as job creation. Pastures are the main source of food for ruminants, however they are not always managed properly. The interactions that occur in the pasture ecosystem are dynamic and complex, involving the relationships between pasture, animal, soil and environment. The sustainable management of a pasture aims to reconcile the qualitative and quantitative aspects of forage production with the efficiency of the animal response by area. Cultivation management practices and grazing intensity are two factors that promote several changes in the morphophysiology of pastures, and these responses vary, primarily, depending on the plant species, genotype, grazing system adopted, grazing pressure and soil nutrition, directly influencing sap allocation and absorption, aerial and root growth, light interception, photosynthetic efficiency and phytomass production. Adjustments and decision making are essential for optimizing production systems, mainly through changes in the environment, in order to provide success in agricultural production, avoiding economic and environmental losses. Thus, the aim of this review was to discuss the influence of environmental modification on plant morphophysiological responses through management practices and adjustments in grazing intensity, as well as to report the impact of these responses on the growth dynamics of forage crops, in which they form the pasture.